To fail an asylum seeker: Time, space and legal events. (February 2022) - Fisher, Dan; Gill, Nick; Paszkiewicz, Natalia
Legal geographers have recently highlighted the importance of attending to the interaction of time and space to understand law and its enactment. We build on these efforts to examine the spatiotemporal influences over the processes by which asylum claim determination procedures in Western industrialised countries seek to reconstruct past events for the purposes of deciding refugee claims. Two 'common-sense' beliefs underpin this reconstruction: that the occurrences leading to a fear of persecution can be isolated and that the veracity of an asylum claim is objectively independent from the process of uncovering it. We critically interrogate these assumptions by conceptualising the fears of people seeking asylum as Deleuzian 'events'. Basing our argument on 41 interviews with people who have previously claimed asylum in the United Kingdom and firsthand accounts of asylum appeals, we explore the folding together of asylum 'truths' and the spatiotemporal processes by which they are arrived at, arguing that refused asylum claims are not simply detected by the process – they are produced by it.